PENGARUH LEVEL KUNING TELUR DALAM PENGENCER TRIS TERHADAP VIABILITAS DAN MOTILITAS SPERMA SEMEN ENTOG (Cairina moschata) - Rifa Nurul Sofa; Siti Darodjah Rasad; Iwan Setiawan (Fakultas Peternakan, Universitas Padjadjaran, 2022)
The purpose of this research was to determine the effect of egg yolk levels in Tris diluents on the viability and motility sperm Muscovy duck (Cairina moshata). This research was conducted from January 11 until February 11 2022. The object of this study was semen from two years old of Muscovy drake. The research applied Completely Randomized Design (CRD) with four treatment levels i.e.: egg yolk by 5% (P1), egg yolk by 10% (P2), egg yolk by 15% (P3), and egg yolk by 20% (P4) with research parameters viability and motility after treatment. The obtained data were analyzed using the ANOVA and Duncan's Multiple Range Test. Based on the results it can be concluded that the addition of egg yolk levels into the Tris diluent affects the viability and motility of sperm. The addition of egg yolk levels 10% in Tris diluents is the best level to produce the optimal viability and motility of Muscovy drake semen (Cairina moschata).